Indium(III) Iodide-Catalyzed Stereoselective Synthesis of β-Glucopyranosides by Using a Glucosyl Fluoride Donor with 2-O-Benzoyl-3,4,6-Tri-O-Benzyl Protection - Ma, Teng; Li, Changwei; Zhang, Zhan-xin; Wang, Zhaoyan; Yu, Lan; Xue, Weihua (Synlett, 2017)
We have developed a novel protocol for glucosylation by adopting a glucosyl fluoride donor with 2-O-benzoyl-3,4,6-tri-O-benzyl protection. The protocol is useful for the ready assembly of β-linked functional glycoconjugates, and the reaction accommodates a broad range of substrates. Conveniently, water-tolerant and commercially available InI3 is used as a catalyst, and no other additional reagent is required. The method involves an interesting process for glucosyl fluoride activation and, in particular, permits the stereoselective construction of partially benzylated glucopyranosides carrying a selectively removable 2-O-benzoyl group, which hold great potential as glycosyl receptors for building further 1,2-glycosidic linkages.
Keywords: indium triiodide; glucopyranosides; glucosyl fluoride; stereoselectivity; benzoylation